Keterampilan Berpikir Kritis Peserta Didik di SMA Negeri 1 Lengayang - Putri, Sonia; Darussyamsu, Rahmawati (TSAQOFAH, 2022)
Critical thinking skills are one of the 21st century skills that students must have to face the challenges of the 21st century. Critical thinking skills make students able to think logically, solve problems appropriately and make rational decisions. Measurement of the level of critical thinking skills of students needs to be done as a benchmark for teachers in honing students' critical thinking skills. This study aims to determine the critical thinking skills of students at SMAN 1 Lengayang. This type of research is descriptive research. The sample in this study were 71 students of class XI SMAN 1 Lengayang. The sampling technique is purposive sampling. The instrument used is a validated questionnaire. Data analysis was done by descriptive analysis. The results showed that the critical thinking skills of students in class XI MIPA at SMAN 1 Lengayang were still low. This can be seen from the percentage of critical thinking skills questionnaire scores of the lowest level (T1) as much as 41.5%, level 2 score (T2) 23.6%, level 3 score (T3) 15.8%, level 4 score (T4) 11%, and a score of level 5 (T5) which is the highest level of 8.5%.